Bacteria derived extracellular vesicles in the pathogenesis and treatment of gastrointestinal tumours - Ge, Yang; Sun, Fengyuan; Zhao, Bo; Kong, Fanyang; Li, Zhaoshen; Kong, Xiangyu (Frontiers in Oncology, 2023)
Extracellular vesicles are fundamentally significant in the communication between cells. Outer Membrane Vesicles（OMVs） are a special kind of EVs produced by Gram-negative bacteria，which are minute exosome-like particles budding from the outer membrane1，which have been found to play essential roles in diverse bacterial life events，including regulation of microbial interactions，pathogenesis promotion，stress responses and biofilm formation2. Recently，more and more researches have explored the substantial potentials of EVs as natural functional nanoparticles in the bioengineering applications in infectious diseases3，cardiovascular diseases，autoimmune diseases and neurological diseases，such as antibacterial therapy，cancer drugs and immunoadjuvants，with several candidates in clinical trials showing promising efficacy4. However，due to the poor understanding of sources，membrane structures and biogenesis mechanisms of EVs，progress in clinical applications still remains timid5. In this review，we summarize the latest findings of EVs，especially in gastrointestinal tract tumours，to provide a comprehensive introduction of EVs in tumorigenesis and therapeutics.